Extracting physics from gravitational waves : testing the strong-field dynamics of general relativity and inferring the large-scale structure of the universe /: testing the strong-field dynamics of general relativity and inferring the large-scale structure of the universe. (2015) - Li, Tjonnie G. F (Tjonnie Guang Feng), 1986-
No abstract available